Moral formation according to Paul : the context and coherence of Pauline ethics - Thompson, James, 1942- (Grand Rapids, Mich. : Baker Academic, 2011)
Leading biblical scholar James Thompson explains that Paul offers a coherent moral vision based not only on the story of Christ but also on the norms of the law. Paul did not live with a sharp dichotomy of law and gospel and recognized the continuing importance of the law. --from publisher description
Introduction : Paul's moral teaching in context -- Ethics in Hellenistic Judaism : maintaining Jewish identity in the diaspora -- Shaping an identity : moral instruction and community formation -- From catechesis to correspondence : ethos and ethics in 1 Thessalonians -- Pauline catechesis and the lists of vices and virtues -- Paul, the law, and moral instruction -- Paul, the passions, and the law -- Putting love into practice -- Ethics and the disputed letters of Paul -- Conclusion: The coherence of Paul's moral teaching.
Includes bibliographical references (p. 215-229) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Ethics in the Bible